2019–2020 Florida Citrus Production Guide: Melanose - Megan M. Dewdney (EDIS)
Management of melanose, caused by the fungus Diaporthe citri, is often necessary in mature groves where fruit is intended for the fresh market, particularly if recently killed twigs and wood are present because of freezes or other causes. Melanose management is not usually needed in groves fewer than 10 years old or in those where fruit is intended for processing. Grapefruit is especially susceptible to melanose but all citrus may be damaged by the disease. This 3-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. Written by Megan M. Dewdney and published by the Plant Pathology Department, March 2019.